Pyrolysis mechanism of isolated microalgal composition and their potential as liquid biofuels: Neutral lipids, phospholipids, glycolipids, and sterols - Yi Wang; Huiyu Qiu; Menghao Zuo; Lu Zuo; Xin Wang; Pengye Song; Shaojie Guo; Boxiong Shen (Energy Conversion and Management: X)
Microalgal lipids are the important feedstock of alternative liquid biofuels due to their similar structure to liquid hydrocarbons and high content in microalgae. However, complex composition of microalgal lipids hinders their practical application as biofuels and their reaction mechanism is also not fully studied, especially for phospholipids and glycolipids. In this study, the key fractions (neutral lipids, phospholipids, and glycolipids) in microalgal lipids were separated by a solid phase extraction method. There was a predominant content (39.5 %) for glycolipids in lipids of microalga Chlorella sp., while there was similar content between the neutral lipids, glycolipids, and phospholipids for microalga Nanochloropsis sp.. The pyrolysis characterization of each lipid fraction was analyzed via pyrolysis–gas chromatography–mass spectrometry. The main carbon number distribution in pyrolysis products were C16, C18, and C20 for all lipid fractions. The main compound types were long-chain chemicals with the carbon number range of C16–C20, especially carboxylic acids. The pyrolysis mechanism was elucidated based on carbon number distribution and compound type distribution in pyrolysis products. The major decomposition reactions were mainly decarboxylation, decarbonylation, glycerol fragmentation, and steroid cracking to form hydrocarbons, acids, and esters. Due to the typical characteristics of sterols in microalgal lipids, the pyrolysis products presented more cyclic structures, especially aromatic hydrocarbons as a typical composition in liquid transportation fuels. This study provide necessary information for large-scale application of microalgal lipids in liquid biofuels via pyrolysis pathway, which is also benefit for the research of novel composite catalysts during catalytic pyrolysis to further upgrading of non-catalytic pyrolysis products.